Active and Fun Learning with Edpuzzle Interactive Learning Video in Elementary School - Wati, Cindy Aprillia Yunita; Jampel, I Nyoman; Suartama, I Kadek (Universitas Pendidikan Ganesha, 2024)
This research is motivated by the low availability of learning media that can support learning in elementary schools. This study aims to determine the design, feasibility and effectiveness of interactive learning video media using edpuzzle for grade III elementary school. This research is a development research with ADDIE development model. The subjects of this research trial were learning material content experts, learning media experts, design experts, third grade elementary school students. The data collection method used questionnaires and tests. The analysis technique used was descriptive quantitative-qualitative. Based on the results of the study, it was obtained that the learning video development design using edpuzzle, namely the stages of analysis, design, development, implementation, evaluation, then the results of product trials by material content experts, learning design experts, learning media experts, individual and small group assessment tests obtained good and very good qualifications. So that the product is declared valid and feasible to use. The effectiveness of the product is calculated based on the results of the paired sample t-test calculation, which shows that there is a significant difference in student learning motivation before using and after using interactive learning video media. So it can be concluded that interactive learning video media using edpuzzle effectively increases student motivation and learning outcomes in grade III elementary school.